Community-centric approaches to kitchen waste management in urban areas for sustainable planning: a systematic review - Abu Bakar, Aniza; Hasan, Sharina Farihah; Muhamad Darus, Fairus (Malaysian Institute of Planners (MIP), 2025)
Kitchen waste is a major contributor to municipal solid waste in urban areas, posing significant environmental and management challenges. This study systematically reviews 29 peer-reviewed articles to assess how community-centric approaches support sustainable kitchen waste management. A mixed-method Systematic Literature Review (SLR), guided by the ROSES protocol, applied deductive thematic coding across five themes: Community Participation and Social Capital (CPS), Governance, Policy and Institutional Frameworks (GPI), Knowledge, Attitudes, and Practices (KAP), Socio-Economic Dimensions (SED), and Cost-Benefit Analysis (CBA). Results show that community participation and trust networks enhance waste separation and recycling, but weak enforcement and fragmented governance undermine sustainability. Awareness of proper practices is widespread, yet an attitude-behavior gap persists, often constrained by convenience, infrastructure, and cultural habits. Socio-economic conditions strongly influence outcomes: low-income and high-density communities face barriers to affordability and space limitations. Cost-benefit perspectives reveal that households are more likely to engage when immediate rewards are provided or visible improvements complement long-term environmental benefits. Kitchen waste management is an integral component of urban planning policy towards sustainability, which requires community engagement, supportive policies, and equitable services to strengthen resilience and inclusivity